Does Anteromedial Portal Drilling Improve Footprint Placement in Anterior Cruciate Ligament Reconstruction?. Issue 7 (July 2016) - Arno, Sally; Bell, Christopher P.; Alaia, Michael J.; Singh, Brian C.; Jazrawi, Laith M.; Walker, Peter S.; Bansal, Ankit; Garofolo, Garret; Sherman, Orrin H.
Abstract: Background: Considerable debate remains over which anterior cruciate ligament (ACL) reconstruction technique can best restore knee stability. Traditionally, femoral tunnel drilling has been done through a previously drilled tibial tunnel; however, potential nonanatomic tunnel placement can produce a vertical graft, which although it would restore sagittal stability, it would not control rotational stability. To address this, some suggest that the femoral tunnel be created independently of the tibial tunnel through the use of an anteromedial (AM) portal, but whether this results in a more anatomic footprint or in stability comparable to that of the intact contralateral knee still remains controversial. Questions/purposes: (1) Does the AM technique achieve footprints closer to anatomic than the transtibial (TT) technique? (2) Does the AM technique result in stability equivalent to that of the intact contralateral knee? (3) Are there differences in patient‐reported outcomes between the two techniques? Methods: Twenty male patients who underwent a bone‐patellar tendon‐bone autograft were recruited for this study, 10 in the TT group and 10 in the AM group. Patients in each group were randomly selected from four surgeons at our institution with both groups demonstrating similar demographics. The type of procedure chosen for each patient was based on the preferred technique of the surgeon. Some surgeons exclusively used the TT technique, whereas other surgeons specifically used the AM technique. Surgeons had no input on which patients were chosen to participate in this study. Mean postoperative time was 13 ± 2.8 and 15 ± 3.2 months for the TT and AM groups, respectively. Patients were identified retrospectively as having either the TT or AM Technique from our institutional database. At followup, clinical outcome scores were gathered as well as the footprint placement and knee stability assessed. To assess the footprint placement and knee stability, three‐dimensional surface models of the femur, tibia, and ACL were created from MRI scans. The femoral and tibial footprints of the ACL reconstruction as compared with the intact contralateral ACL were determined. In addition, the AP displacement and rotational displacement of the femur were determined. Lastly, as a secondary measurement of stability, KT‐1000 measurements were obtained at the followup visit. An a priori sample size calculation indicated that with 2n = 20 patients, we could detect a difference of 1 mm with 80% power at p < 0.05. A Welch two‐sample t‐test (p < 0.05) was performed to determine differences in the footprint measurements, AP displacement, rotational displacement, and KT‐1000 measurements between the TT and AM groups. We further used the confidence interval approach with 90% confidence intervals on the pairwise mean group differences using a Games‐Howell post hoc test to assess equivalence between the TT and AM groups for the previously mentioned measures. Results: The AM and TT techniques were the same in terms of footprint except in the distal‐proximal location of the femur. The TT for the femoral footprint (DP%D) was 9% ± 6%, whereas the AM was −1% ± 13% (p = 0.04). The TT technique resulted in a more proximal footprint and therefore a more vertical graft compared with intact ACL. The AP displacement and rotation between groups were the same and clinical outcomes did not demonstrate a difference. Conclusions: Although the AM portal drilling may place the femoral footprint in a more anatomic position, clinical stability and outcomes may be similar as long as attempts are made at creating an anatomic position of the graft. Level of Evidence: Level III, therapeutic study.